‘And Yet, What Would We Be Without Memory?’ Visualizing Memory in Two Canadian Graphic Texts - Drewniak, Dagmara (Studia Anglica Posnaniensia, 2018)
Since “we live in a culture of confession” (Gilmore 2001: 2; Rak 2005: 2) a rapidly growing popularity of various forms of life writing seems understandable. The question of memory is usually an important part of the majority of autobiographical texts. Taking into account both the popularity of life writing genres and their recent proliferation, it is interesting to see how the question “what would we be without memory?” (Sebald 1998 [1995]: 255) resonates within more experimental auto/biographical texts such as a graphic memoir/novel I Was a Child of Holocaust Survivors (2006) by Bernice Eisenstein and a volume of illustrated poetry and a biographical elegy published together as Correspondences (2013) by Anne Michaels and Bernice Eisenstein. These two experimental works, though representing disparate forms of writing, offer new stances on visualization of memory and correspondences between text and visual image. The aim of this paper is to analyze the ways in which the two authors discuss memory as a fluid concept yet, at the same time, one having its strong, ghostly presence. The discussion will also focus on the interplay between memory and postmemory as well as correspondences between the texts and the equally important visual forms accompanying them such as drawings, portraits, sketches, and the bookbinding itself.